Hubungan antara dukungan Sosial dengan Stres Kerja Karyawan Di CV. Buana Pilar Mandiri - Shely Mulia Sari; Hairul Anwar Dalimunthe (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2023)
This study aims to determine the correlations between social support and employee job stress at CV. Buana Pillar Mandiri. The type of research used in this study is a quantitative approach. The population in this study were 72 permanent employees CV. Buana Pillar Mandiri. The technique used by researchers is Total Sampling. The results of a negative correlation between social support and work stress, with a correlation coefficient of rxy = -0.594, with a significant p = 0.000 0.05, meaning that the hypothesis is accepted. The determinant coefficient (r2) of the relationship between the independent variable and the variable is r2= 0.352. This shows that social support is distributed by 35.20% of work stress. This shows that there are 64.80% other factors that influence work stress such as: work intrinsic factors, workload, individual roles, career development, relationships in work, organizational structure, from outside the organization and individual characteristics. Based on the mean test, it can be seen that social support obtained moderate results. Furthermore, the overall work stress results are moderate.